Phase Angle Is Moderately Associated With Muscle Quality and Functional Capacity, Independent of Age and Body Composition in Older Women - Tomeleri, Crisieli M. (2019)
Background and purpose: There is a growing body of evidence indicating that phase angle (PhA) can be used as an indicator of nutritional status, disease prognosis, and mortality risk; however, it is still unknown whether PhA can be used as an explanator of functional capacity and muscle quality in older women. The main purpose of this cross-sectional study was to explore whether PhA is associated with muscle quality and functional capacity in older women, regardless of total and regional body composition. Methods: A total of 125 older women-66.7 (4.7) years; 65.6 (10.9) kg body mass; 156.1 (5.2) cm height; 26.9 (4.0) kg/m(2) body mass index-participated in this study. Anthropometric, PhA, body composition (whole-body dual-energy x-ray absorptiometry) and muscle quality (defined as total muscular strength per kilogram of appendicular lean soft tissue) were measured. The functional capacity was assessed by 4 tests: 10-m walk test, rising from sitting position, rising from ventral decubitus position, and rising from a chair and walking around the house. The summing z-scores for the 4 tests was used as a continuous functional capacity score. Linear regression analysis was conducted to test whether PhA is related to the dependent variables (muscle quality and functional capacity), after adjusting for potential covariates. Results: The PhA presented a small-to-moderate relationship with muscle quality (r = 0.27; P <.01) and functional capacity (r = 0.31; P <.01), respectively. These relationships remained significant after adjustment for age, lower limb lean soft tissue, and total fat mass for muscle quality (beta = 0.55; P <.01) and functional capacity (beta = 1.38; P <.01). Conclusion: Our findings suggest that healthy elderly women with higher values of PhA have a better muscle quality and functionality, regardless of age and body composition.